2001
DOI: 10.4049/jimmunol.166.7.4728
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Transfected with Adenovirus to Express IL-4 Reduce Inflammation in Experimental Glomerulonephritis

Abstract: Nephrotoxic nephritis (NTN) is characterized by acute macrophage-dependent inflammation and serves as a model of human glomerulonephritis. In this study we have transfected rat macrophages with recombinant adenovirus expressing IL-4 (Ad-IL4) and demonstrated that these transfected macrophages develop fixed properties as a result of transfection, as shown by reduced NO production in response to IFN-γ and TNF. Ad-IL4-transfected macrophages localized with enhanced efficiency to inflamed glomeruli after renal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…Macrophages transfected with adenovirus expressing IL-4 ex vivo reduced macrophage infiltration and albuminuria in an experimental model of GN. 31 However, this type of ex vivo gene transfer is both laborious and expensive because it requires the isolation, growth, and transduction of primary macrophages from each rat. Adenovirus vector, moreover, induces an immune response and causes side effects that render its repeated administration problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages transfected with adenovirus expressing IL-4 ex vivo reduced macrophage infiltration and albuminuria in an experimental model of GN. 31 However, this type of ex vivo gene transfer is both laborious and expensive because it requires the isolation, growth, and transduction of primary macrophages from each rat. Adenovirus vector, moreover, induces an immune response and causes side effects that render its repeated administration problematic.…”
Section: Discussionmentioning
confidence: 99%
“…NTN is a robust model of macrophage-dependent injury in which there are reliable methods for quantifying infiltrating leukocytes and characterizing their phenotype (23,24). It was therefore ideal for analyzing SOCS protein expression in infiltrating macrophages.…”
Section: Macrophages Selectively Express Socs1 or Socs3 In Inflamed Gmentioning
confidence: 99%
“…We have previously shown that a high local concentration of IL-4 in the glomerulus, induced by IL-4 over-expressing macrophages, significantly reduced the severity of renal injury as assessed by glomerular macrophage number and albuminuria (24). Kidney sections from these experiments were re-analyzed to determine the total number glomerular macrophages and the number expressing SOCS1 and SOCS3.…”
Section: Socs3 Expressing Macrophages Are Essential For Acute Glomerumentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of NR8383 macrophages into normal rat glomeruli via renal artery perfusion induces a number of pro-inflammatory responses, which are not seen when the function of the transcription factor nuclear factor-B (NF-B) is inhibited in the transferred macrophages (10). In addition, the transfer of macrophages modified to secrete antiinflammatory cytokines (IL-1ra, IL-4, or IL-10) has been shown to suppress renal injury in animal models of anti-GBM disease (11)(12)(13). However, it is not clear whether this suppression of renal injury is due to modulation of macrophage function and/or effects of the secreted cytokines upon intrinsic renal cells and other leukocytes.…”
mentioning
confidence: 99%